Answer :
The solution to the problem is as follows:
The quotient rule is ( f'(x)g(x)-f(x)g'(x) )/ (g(x))^2 {complex written on 1 line I know}
let f(x)=9x +13 and g(x)=2x+4
f'(x)=9 and g'(x)=2
therefore just substitute the equations in.
y'= 6x - ((9(2x+4)-2(9x+13))/((2x+4)^2))
I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!
The quotient rule is ( f'(x)g(x)-f(x)g'(x) )/ (g(x))^2 {complex written on 1 line I know}
let f(x)=9x +13 and g(x)=2x+4
f'(x)=9 and g'(x)=2
therefore just substitute the equations in.
y'= 6x - ((9(2x+4)-2(9x+13))/((2x+4)^2))
I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!